Larangan Balap Liar di Kota Padangsidimpuan - Andi Mulia Lubis; Sumper Mulia Harahap (Jurnal El-Thawalib, 2022)
This study discusses the implementation of Law No. 22 of 2009 article 115 concerning the prohibition of racing with other motorized vehicles in the city of Padangsidimpuan. This research is motivated by the number of teenagers who are racing with motorcycles, especially on Jl. Gen. Besar A Haris Nasution in the city of Padangsidimpuan causing problems of security, order and public comfort on Jl. Gen. Besar A Haris Nasution This research is a field research using qualitative descriptive analysis method. Wild racing has become a teenager’s habit that is hard to leave. The data collection method in this study was by interview and documentation in accordance with the provisions contained in Government Regulation Number 22 of 2009 article 115 concerning the prohibition of racing with other motorized vehicles. Law No. 22 of 2009 article 115 concerning the prohibition of racing with other motorized vehicles in the city of Padangsidimpuan has not been implemented optimally, this can be seen from the data on the existence of many teenagers who do illegal racing. And when viewed from the fiqh siyasa of the government in overcoming Law No. 22 of 2009 article 115 concerning the prohibition of racing with other motorized vehicles in the city of Padangsidimpuan